The impact of public opinion on board structure changes, director career progression, and CEO turnover: evidence from CalPERS' corporate governance program - Wu, YiLin (Journal of Corporate Finance, 2004)
Extant research investigates the effects of legal mechanisms and shareholder activism on corporate governance. Zingales [Journal of Finance 55 (2000) 1623] calls for research concerning the effects of public opinion on corporate governance. The California Public Employees' Retirement System (CalPERS) influences public opinion by publicly naming the companies having poor corporate governance. This study hypothesizes that public naming by CalPERS damages the reputations of management and directors at these companies, and these companies respond by improving their corporate governance. This hypothesis is supported by three findings. First, companies are more likely to decrease the number of inside directors after being named publicly by CalPERS. A large proportion of departing inside directors remains full-time employees in the named companies. Second, departing inside directors are less likely to take up future directorships after their companies are named publicly by CalPERS. Finally, the likelihood of CEO dismissal increases and the relation between performance and CEO dismissal becomes stronger after companies are named publicly by CalPERS. These three findings are consistent with the hypothesis that CalPERS influences public opinion and that reputation concerns are effective in compelling companies to improve their corporate governance system.